2014
DOI: 10.1108/jrme-06-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

Identifying entrepreneurs through risk taking behaviour: illegal downloading

Abstract: Purpose – This paper aims to explore, and is the first in a series, whether it is possible to use risk-taking activities as way of identifying potential entrepreneurs. The research examines the motivations of individuals to engage in deviant consumer behaviour, in this case illegal downloading and the link between this behaviour and possible entrepreneurial characteristics. Design/methodology/approach – The methodology approach was of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
3
5
1
Order By: Relevance
“…Students who have necessary skills coupled with adequate resources will choose entrepreneurship as their career. Even though risk-taking propensity is always linked to entrepreneurship (Pascor & Mortimer, 2014), the finding in this study is contradictory. However, innovativeness is found to be one of the factors that affect students' entrepreneurial intentions.…”
contrasting
confidence: 52%
“…Students who have necessary skills coupled with adequate resources will choose entrepreneurship as their career. Even though risk-taking propensity is always linked to entrepreneurship (Pascor & Mortimer, 2014), the finding in this study is contradictory. However, innovativeness is found to be one of the factors that affect students' entrepreneurial intentions.…”
contrasting
confidence: 52%
“…New venture development has for a long time been recognized as a risky undertaking, from professional, personal and financial perspectives (Mullins et al , 2002; Pascoe and Mortimer, 2014). Past research indicates that the creation and management of a startup enterprise is a highly stressful form of occupation (Lofstrom et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However the strength of such a relationship has been challenged. For example, Pascoe and Mortimer (2014), using a student sample, found that while risk taking is correlated with entrepreneurial traits, it is not related to illegal downloading of content from the internet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The participants are therefore likely to be able to analyse problems, identify opportunities for solving them, have the skills to generate ideas and make decisions, are able to develop a strategic vision for solutions, and maintain a sufficient degree of ethical thinking, as evidenced by actions to achieve goals. It is assumed that entrepreneurial activity and the initiation thereof requires a fairly high level of investment with a high level of risk because the success of any initiative depends on entrepreneurial competencies in the field of resource management [24,26]. For the cluster "Resources", and based on the scope diagram in Figure 4, it can be said that the results of the assessments in the two populations is fairly similar.…”
Section: Main Results Of the Researchmentioning
confidence: 99%
“…Learning and developing as a person is an important component of entrepreneurial competence [6,27]. The same can be said about the manifestation of initiative [26], planning and management [5], risk management [21], and interaction with people [5,6]. For the competencies in the cluster "Into action", the assessment focuses on the students´ ability to act and apply their knowledge and skills in various situations (see Figure 5).…”
Section: Main Results Of the Researchmentioning
confidence: 99%